Peran Insentif dan Motivasi terhadap Kinerja Karyawan PT. Sagara Xinix Solusitama - Muhammad Naufal; Lingga Yuliana (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
The purpose of this study is to analyze the role of incentives and motivation in influencing employee performance at PT. Sagara Xinix Solusitama. This study also aims to provide an overview of whether the incentive and motivation system implemented by the company has been effective in increasing employee work productivity. This study uses a qualitative approach with data collection techniques in the form of interviews. Purposive Sampling is the sampling technique in this study. Based on the results of the study and the discussion above, it can be concluded that the incentive system implemented by the company has a positive impact on employee motivation and performance. Incentives, both financial such as bonuses and allowances, and non-financial such as training and awards, have been proven to be able to increase work enthusiasm, loyalty, and a sense of belonging to the company. This study also shows that the effectiveness of incentives is not only determined by the nominal or type, but also by the extent to which the incentives are given fairly, transparently, and relevant to individual contributions. The subjective perception of each employee plays an important role in assessing how much incentives can encourage them to work better.